Mitochondria and Human Cancer - Modica-Napolitano, Josephine S.; Kulawiec, Mariola; Singh, Keshav K. (Current Molecular Medicine, 2007)
The better part of a century has passed since Otto Warburg first hypothesized that unique phenotypic characteristics of tumor cells might be associated with an impairment in the respiratory capacity of these cells. Since then a number of distinct differences between the mitochondria of normal cells and cancer cells have been observed at the genetic, molecular, and biochemical levels. This article begins with a general overview of mitochondrial structure and function, and then outlines more specifically the metabolic and molecular alterations in mitochondria associated with human cancer and their clinical implications. Special emphasis is placed on mtDNA mutations and their potential role in carcinogenesis. The potential use of mitochondria as biomarkers for early detection of cancer, or as unique cellular targets for novel and selective anti-cancer agents is also discussed.
Keywords: TCA cycle